Analyzing the Role of Internal Control System in Maintaining Unqualified Opinion (WTP) in Local Government Financial Statements - Fathiyah Fathiyah; Marissa Putriana (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2020)
This study analyzes the role of Internal Control System (SPI) in maintaining unqualified opinions on the Jambi Provincial Government Financial Statements. A descriptive comparative method is used with a qualitative approach. The object of the study is the Internal Control System in the Jambi Provincial Government Financial Statements of 2016-2018. Data is analysed using the selection technique before drawing conclusions. The results show that the Internal Control System in Jambi Provincial Government Financial Statements is very weak. The system has not been effective in its implementation because there are still findings related to SPI by the Supreme Audit Agency (BPK) every year. Therefore, it is necessary to follow up on the recommendations of BPK to build a better SPI in the future. This should be based on the elements of the internal control system contained in Government Regulation Number 60 of 2008, including control environment and activities, risk assessment, information and communication, and monitoring.